A study of scale development on determination of pre-service and in-service teachers’ beliefs about pre-school mathematics education - Bülent GÜVEN; İlhan KARATAŞ and Yasin ÖZTÜRK and Selahattin ARSLAN and Kadir GÜRSOY (Elementary Education Online, 2023)
There is a global movement toward increasing the number of early childhood education services for young children. Through early education, children’s development will be supported. It can be asserted that mathematical experiences of the children in pre-school education not only change their attitudes related to mathematics but also develop their mathematics learning significantly. Therefore, it is claimed that the beliefs of pre-school teachers or pre-service pre-school teachers related to the mathematics, mathematics education and learning of mathematics have a direct effect on children’s mathematics experiences. In this study, a scale is developed in order to determine the beliefs of pre-school teachers or pre-service early childhood education teachers related to the mathematics, mathematics education and learning of mathematics. A factor analysis is done by implementing a belief scale consisting of 74 items on 456 pre-service teachers. A belief scale of 32 items is prepared with respect to the results.